2017
DOI: 10.21577/1984-6835.20170036
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Evaluation of the Orange Peel Adsorptive Properties in the Dye Direct Blue 86 Removal

Abstract: Abstract:The use of powdered from orange peel (Citrus sinensis) as low cost adsorbent for the removal of the dye Direct Blue 86, routinely used in the textile industry, was the objective of this work. A porous structure compatible with the adsorption of molecules with dimensions of up to 15 micrometers was verified in the characterization of the orange peel powder (OPP). The OPP answered the ABNT NBR 2133 norm showing lower humidity content of 8%. The ash content indicated few impurities in the material, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
(3 reference statements)
0
1
0
1
Order By: Relevance
“…Este valor está de acordo com o apontado por Freitas et al (2016), em que o valor de pH encontrado foi realizado com a média aritmética dos pontos em que o pH se manteve constante, resultando em um valor 6,72. Formica et al (2017), investigou as propriedades adsortivas da casca da laranja e o valor de PCZ encontrado foi de 6,53 baseado em um gráfico feito com a diferença dos valores de pH inicial e final.…”
Section: Resultsunclassified
“…Este valor está de acordo com o apontado por Freitas et al (2016), em que o valor de pH encontrado foi realizado com a média aritmética dos pontos em que o pH se manteve constante, resultando em um valor 6,72. Formica et al (2017), investigou as propriedades adsortivas da casca da laranja e o valor de PCZ encontrado foi de 6,53 baseado em um gráfico feito com a diferença dos valores de pH inicial e final.…”
Section: Resultsunclassified
“…This value is that pointed out by Freitas et al (2016), the pH value found was performed with the arithmetic mean of the points at which the pH remained constant, resulting in a value of 6.72. In Formica et al (2017), we worked on the adsorptive properties of the orange peel and the PCZ value found was 6.53 based on a graph made with the difference of the initial and final pH values.…”
Section: A Look At Developmentmentioning
confidence: 99%